The evolutionary assembly of neuronal machinery - Arendt, Detlev (Current biology, 2020)
Neurons are highly specialized cells equipped with a sophisticated molecular machinery for the reception, integration, conduction and distribution of information. The evolutionary origin of neurons remains unsolved. How did novel and pre-existing proteins assemble into the complex machinery of the synapse and of the apparatus conducting current along the neuron? In this review, the step-wise assembly of functional modules in neuron evolution serves as a paradigm for the emergence and modification of molecular machinery in the evolution of cell types in multicellular organisms. The pre-synaptic machinery emerged through modification of calcium-regulated large vesicle release, while the postsynaptic machinery has different origins: the glutamatergic postsynapse originated through the fusion of a sensory signaling module and a module for filopodial outgrowth, while the GABAergic postsynapse incorporated an ancient actin regulatory module. The synaptic junction, in turn, is built around two adhesion modules controlled by phosphorylation, which resemble septate and adherens junctions. Finally, neuronal action potentials emerged via a series of duplications and modifications of voltage-gated ion channels. Based on these origins, key molecular innovations are identified that led to the birth of the first neuron in animal evolution.